ECOLOGICAL STUDIES ON MACROZOOBENTHIC COMMUNITIES OF SOFT-BOTTOMS OF THE NORTHERN ADRIATIC SEA, AROUND THREE OFF-SHORE OIL PLATFORMS - Trabucco, Benedetta (Biologia Marina Mediterranea, 2024)
The oil industry has spread all over the globe, since the worldwide increase in energy demand has strongly increased the exploitation of non-renewable resources. ISPRA (Italian Institute for Environmental Protection and Research) has been implementing environmental monitoring plans for more than two decades to evaluate the potential effects induced on the marine ecosystem by off-shore activities in the Upper Adriatic. In the ISPRA X0PIATPE Project, data on the macrofauna of soft bottoms were collected at different distances from different off-shore gas platforms. The macrozoobenthic communities studied, locally around three platforms, and regionally in three related areas, generally show quality and quantitative structural characteristics comparable to those described in these Mediterranean zones. However, the communities settled immediately in the area adjacent to the structures appear enriched by elements not directly attributable to the mobile sediments, compared to those found in the more distant stations.